Decadal variation in the heat and cold waves over India during 1971-2000 - PAI, D. S.; THAPLIYAL, V.; KOKATE, P. D. (MAUSAM, 2004)
Using information regarding daily heat wave and cold wave conditions over all the meteorological sub-divisions of India for the period 1971-2000, the decadal changes in the various characteristics of heat wave (HW)/severe heat wave (SHW) and cold wave (CW)/severe cold wave (SCW) were examined. A significant increase was noticed in the frequency, persistency and spatial coverage of both of these high frequency temperature extreme events (heat and cold waves) during the decade (1991-2000). These changes might be the manifestation of regional impact of highest ever decadal scale global warming recorded during the period (1991-2000). A part of these changes might also be caused by local factors such as deforestation, urbanization etc. The HW/SHW activity over most of the subdivisions were relatively less during the intermediate decadal period (1981-1990) as compared to that during the preceding (1971-1980) and succeeding (1991-2000) decadal periods. The CW/SCW activity over North India showed increase from the decade of seventies to eighties and then to nineties. For other areas, the changes in the CW/SCW activity were similar to that of HW/SHW with the intermediate period having minimum activity compared to the other two periods. During the entire data period, three sub-divisions, namely Kerala, Lakshadweep and Andaman & Nicobar Islands did not experience any heat/cold wave conditions at all.